PARENTS’ AND CHILDREN’S LANGUAGE IN A BILINGUAL COMMUNITY IN SLEMAN - Ismiati Ismiati (Conscientia, 2021)
This paper aims at describing the parent-children’s language in a bilingual community in Sleman. Bilingual parents of Bahasa Indonesia and Javanese were observed when they were having conversations with their children. This research wanted to find out the parents-and-children’s language in their communication at home.  Therefore, this research attempted to find the answers to the following research objectives: (1) the language that the bilingual parents use to communicate with their children; (2) the parents’ background and perception in using the language.  This research used observations and interviews as the methods for data collection.  As for the analysis, the data was analyzed using the descriptive quantitative method.  The participants of this research were of ten families of Javanese ethnic with children who lived in Sleman.  The result shows that the language use in the parents-children conversation tends to use Bahasa (60%) rather than Javanese (40%).  Parents with lower education and manual works use Javanese and families with higher education and office works use Indonesia.